Impact of Amarogentin on Gastric Carcinoma Cell Multiplication, Apoptosis and Migration via circKIF4A/miR-152-3p - Zhi Tan; Weining Wang; Jin Peng; Zhen Zhou; Jia Pan; Aiming Peng; Hui Cao; Wenling Fan (Journal of Immunology Research)
Objective. The active ingredients extracted from natural plants have anti-GC actions and can slow down gastric carcinoma (GC) progression. To investigate the impact of Amarogentin (AG) on GC cell multiplication, apoptosis and migration and the possible mechanisms. Methods. qRT-PCR quantification of circKIF4A and miR-152-3p in GC tissues and normal counterparts as well as HGC-27 (human GC cell strain) and GES-1 (human gastric mucosal epithelial cell strain) was performed. HGC-27 cells were intervened by AG of various concentrations. si-NC, si-circKIF4A were further transfected into HGC-27 cells. Besides, pcDNA and pcDNA-circKIF4A were transfected into HGC-27 cells, after which 60 mmol/L AG was added for intervention. Cell multiplication, clone formation, as well as apoptosis and migration measurements were made by MTT, plate clone formation, flow cytometry and Transwell assays, respectively; Double luciferase reporter assay was performed for targeting relationship identification between circKIF4A and miR-152-3p; Western blots were carried out to measure Bax and Bcl-2 protein levels. Results. circKIF4A increased (P <0.05) and miR-152-3p decreased (P <0.05) in GC tissues and cell strains. Concentration-dependently, AG intervention contributed to enhanced cell multiplication inhibitory rate, apoptosis rate, miR-152-3p expression and Bax protein level (P <0.05), together with declined number of cell clones formed, migrating cells, circKIF4A expression and Bcl-2 protein level (P <0.05). After transfection of si-circKIF4A, cell multiplication inhibition rate, apoptosis rate and Bax protein level enhanced (P <0.05), while cell clones formed and migrating cells as well as Bcl-2 protein level reduced (P <0.05). miR-152-3p can be controlled by circKIF4A; pcDNA-circKIF4A transfection antagonized AG’s effects on HGC-27 cell multiplication, clone formation, apoptosis and migration. Conclusion. AG can decrease GC multiplication, clone formation and migration and induce apoptosis via modulating circKIF4A/miR-152-3p expression.